1998
DOI: 10.1039/a803140a
|View full text |Cite
|
Sign up to set email alerts
|

Radiation chemistry of D2O Time dependence of the yields of the radicals at ambient temperature and rate constants for the reactions OD+OD and D+OD up to 200°C

Abstract: 6QB The yields of and have been measured in at ambient temperature as a function of e aq~, e aq~]~O D e aq~] D~]~OD D 2 O scavenger concentration. At scavenging powers O107 s~1 is 10% larger than its value in but for scavenging powers G(e aq~) H 2 O, P3 ] 108 s~1 the yields of and are the same in both solvents, indicating that scavenging in e aq~, e aq~]~O D e aq~] D~]~OD the spurs suppresses the reactions leading to the di †erent primary yields. The absorption spectrum of is found to be verỹOD similar to that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…(Nevertheless very similar results have been found for the longest spur decay component using lower dose 2 ns electron pulses at the Notre Dame Radiation Laboratory , The very low scavenging power data of Buxton et al shown in Figure could be matched by exchanging the constant 1 in eq 9 for an additional exponential decay with time constant of about 13 μs. Our time-resolved experiment is insensitive to such a slow component of track chemistry.…”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations
“…(Nevertheless very similar results have been found for the longest spur decay component using lower dose 2 ns electron pulses at the Notre Dame Radiation Laboratory , The very low scavenging power data of Buxton et al shown in Figure could be matched by exchanging the constant 1 in eq 9 for an additional exponential decay with time constant of about 13 μs. Our time-resolved experiment is insensitive to such a slow component of track chemistry.…”
Section: Resultssupporting
confidence: 66%
“…We consider the work of Elliot et al using both nitrate and methyl viologen scavengers, as perhaps the most reliable in the literature. Recent work of Buxton et al has shown good agreement for both N 2 O and tetranitromethane scavengers. The precise methyl chloride measurement of Schmidt et al, which was based entirely on conductivity including a T-jump for dosimetry, is also in superb agreement with the predicted curve.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Elliot and co-workers measure 3.0−3.2 electrons/100 eV. Buxton and co-workers obtain 3.1 electrons /100 eV . Fielden and Hart measured 3.0 for this quantity, also at a scavenging power of 10 7 s -1 .…”
Section: Resultsmentioning
confidence: 91%